![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1:
a)10/20-15/20+16/20=-5/20+16/20
=11/20.
b)2/3+8/3:8/5=2/3+5/3
=7/3.
2:a)Ta có:
2x=1/4=3/4
2x=4/4=1
x=1:2
x=0,5
b)x:(2/12-1/12)=-3/8.
x:1/12=-3/8.
x=-3/8x1/12.
x=-1/32.
![](https://rs.olm.vn/images/avt/0.png?1311)
a ) \(5\left(x^2\right)+7x+2\)
\(\Leftrightarrow5x^2+7x+2=0\)
\(\Leftrightarrow5x^2+5x+2x+2=0\)
\(\Leftrightarrow\left(5x+2\right)\left(x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{2}{5}\\x=-1\end{matrix}\right.\)
Vậy .............
b ) \(\dfrac{x+1}{17}+\dfrac{x+2}{16}=\dfrac{x+3}{15}+\dfrac{x+4}{14}\)
\(\Leftrightarrow\dfrac{x+1}{17}+1+\dfrac{x+2}{16}+1=\dfrac{x+3}{15}+1+\dfrac{x+4}{14}+1\)
\(\Leftrightarrow\dfrac{x+18}{17}+\dfrac{x+18}{16}=\dfrac{x+18}{15}+\dfrac{x+18}{14}\)
\(\Leftrightarrow\dfrac{x+18}{17}+\dfrac{x+18}{16}-\dfrac{x+18}{15}-\dfrac{x+18}{14}=0\)
\(\Leftrightarrow\left(x+18\right)\left(\dfrac{1}{17}+\dfrac{1}{16}-\dfrac{1}{15}-\dfrac{1}{14}\right)=0\)
Vì \(\left(\dfrac{1}{17}+\dfrac{1}{16}-\dfrac{1}{15}-\dfrac{1}{14}\right)\ne0\)
Ta có : \(x+18=0\Leftrightarrow x=-18\)
Vậy ......
c ) \(\dfrac{x-1}{x-3}=\dfrac{x-4}{x-7}\)
\(\Leftrightarrow\left(x-1\right)\left(x-7\right)=\left(x-3\right)\left(x-4\right)\)
\(\Leftrightarrow x^2-7x-x+7=x^2-4x-3x+12\)
\(\Leftrightarrow-x=5\)
\(\Leftrightarrow x=-5\)
Vậy ..
![](https://rs.olm.vn/images/avt/0.png?1311)
a) -5(x - 3) - 2(5 - 3x) = -(x - 1)
=> -5x + 15 - 10 + 6x = -x + 1
=> x + 5 = -x + 1
=> x + x = 1 - 5
=> 2x = -4
=> x = -4 : 2
=> x = -2
\(-5\left(x-3\right)-2\left(5-3x\right)=-\left(x-1\right)\)
\(\Leftrightarrow-5x+15-10+6x=-x+1\)
\(\Leftrightarrow x+5=1-x\)
\(\Leftrightarrow2x=-4\)
\(\Leftrightarrow x=-4\div2\)
\(\Leftrightarrow x=-2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(2\left(x-3\right)-3\left(x-1\right)=2x+6\)
\(\Leftrightarrow2x-6-3x+3=2x+6\)
\(\Leftrightarrow-3x=9\Leftrightarrow x=-3\)
Vậy x=-3
b) \(2\left(x+7\right)-4\left(x-2\right)=10\)
\(\Leftrightarrow2x+14-4x+8=10\)
\(\Leftrightarrow-2x=-12\Leftrightarrow x=-6\)
Vậy x=-6
c) \(10-\left(1-x\right)^2=6\Leftrightarrow\left(1-x\right)^2=4\)
\(\Leftrightarrow\left[\begin{matrix}1-x=-2\\1-x=2\end{matrix}\right.\Leftrightarrow\left[\begin{matrix}x=3\\x=-1\end{matrix}\right.\)
Vậy x=3 hoặc x=-1
d)\(\left(x-3\right)^3-\left[\left(-2\right)^3+2^3\right]\left(1+3+5+7+...+2001\right)=-512\)
\(\Leftrightarrow\left(x-3\right)^3=-512\)
\(\Leftrightarrow x-3=-8\Leftrightarrow x=-5\)
Vậy x=-5
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\Leftrightarrow x\left(-\dfrac{7}{2}-\dfrac{5}{4}\right)=\dfrac{1}{4}\cdot\dfrac{-4}{3}+\dfrac{1}{6}+\dfrac{3}{4}\)
\(\Leftrightarrow x\cdot\dfrac{-19}{4}=\dfrac{7}{12}\)
hay x=-7/57